Penguatan Komunitas Belajar Guru dengan Teknologi Digital: Studi Kasus KKG Malabiri - Hanapi, Sitti Harlina; Layuk, Novita Sambo; Patasik, Madyana; Akhriana, Asmah; Samsuddin, Sadly; Usman, Usman; Djafar, Imran; Rizal, Muhammad; Rahmat, Rahmat (Jurnal Pengabdian kepada Masyarakat UBJ, 2025)
To improve the digital skills of teachers in KKG Malabiri, a community service program was held, focusing on the use of Google Form and Canva in creating interactive assessment and learning materials. Through a one-day intensive training, 56 elementary school teachers from Minasatene District, Pangkajene Islands Regency, managed to show a significant increase in their understanding, as evidenced by an increase in the average score from 42.1 to 80.9. This program confirms the effectiveness of hands-on training in equipping teachers with relevant digital skills. Through the community service program, teachers in KKG Malabiri received intensive training in the use of Google Form and Canva, which aims to improve their ability to create interactive assessment and learning media. The training, which involved 56 elementary school teachers from Minasatene District, Pangkajene Islands Regency, managed to significantly improve their understanding, with an increase in the average score from 42.1 to 80.9